The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.fss.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Interpretability of fuzzy linguistic summaries

Abstract: This paper investigates the question of the interpretability of fuzzy linguistic summaries, both at the sentence level and at the summary level, seen as a set of sentences. The individual sentence interpretability is examined as depending both on its representativity measured by a quality degree and on its linguistic expression. Different properties at the summary level are also discussed, namely their consistency, their non redundancy and the information they convey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In this work, we apply the basic structure of linguistic summaries (2), evaluations expressed by the quantifier most of Kacprzyk and Zadrożny (2005), that is further parametrized in Hudec (2016) and aggregation functions (Beliakov et al, 2007), in order to explore the raised research questions. A review of the other types of linguistic summaries can be found in Lesot et al (2016), whereas a review of applicability can be found in Boran et al (2016). The solution of a summary is the validity or truth value of the evaluated quantified sentence, not a set of retrieved entities from (1).…”
Section: Linguistic Summaries In Briefmentioning
confidence: 99%
“…In this work, we apply the basic structure of linguistic summaries (2), evaluations expressed by the quantifier most of Kacprzyk and Zadrożny (2005), that is further parametrized in Hudec (2016) and aggregation functions (Beliakov et al, 2007), in order to explore the raised research questions. A review of the other types of linguistic summaries can be found in Lesot et al (2016), whereas a review of applicability can be found in Boran et al (2016). The solution of a summary is the validity or truth value of the evaluated quantified sentence, not a set of retrieved entities from (1).…”
Section: Linguistic Summaries In Briefmentioning
confidence: 99%
“…However, among other interesting fuzzy models, we would like to focus on linguistic summaries [7] [8], that combine the understandability of simplified natural language and the capacities of automatic learning and quality checking, the quality being understood in various senses. Their purpose is to sum up information contained in large volumes of data into simple sentences and the interpretability is at the core of the process [9]. The most generally used sentences, called protoforms, are of the form "Q B x s are A", where Q is a fuzzy quantifier representing a linguistic quantifier such as "most" or "a majority of", or, in the case of time series, a temporal indication such as "often" or "regularly", B is a fuzzy qualifier of elements x of the dataset to be summarised, sometimes omitted, and A is a fuzzy description of these elements called a summariser.…”
Section: Linguistic Summariesmentioning
confidence: 99%
“…One of their main advantage is human-consistency. In [18], Lesot et al investigate the interpretability of fuzzy linguistic summaries, both at the sentence level and at the group of summaries level.…”
Section: Related Workmentioning
confidence: 99%